Gastrointestinal hormone levels and their dynamics on the background of enzyme replacement therapy in patients with chronic pancreatitis and type 2 diabetes mellitus - Ye.S. Sirchak (Gastroenterologìa, 2021)
Background. The debate over the relationship between chronic pancreatitis (CP) and diabetes mellitus (DM) has been going on for a long time. However, it has not received enough attention in the existing consensus, and the formulated provisions lack higher-level evidence. The purpose was to determine changes in the level of gastrointestinal hormones (GIH) in the serum and their dynamics against the background of enzyme replacement therapy in patients with CP and type 2 diabetes mellitus. Materials and methods. Ninety-two patients with CP and DM2 were examined. The patients were divided into 2 groups: group I (n = 40) patients received an enzyme preparation with a minimum of 10,000 PhEur units lipase activity for the correction of exocrine pancreatic insufficiency (EPI) and group II (n = 52) of patients with a minimum lipase activity of 25,000 PhEur units 3 times a day for a month. The dynamics of gastrin, somatostatin, cholecystokinin levels was determined in patients before and after the treatment. Results. Analysis of the GIH levels in the serum of patients with CP and DM2 before treatment indicates their changes compared with the control group, namely a statistically significant decrease in gastrin (p < 0.01) and cholecystokinin (p < 0.05), and increased serum somatostatin levels (p < 0.05). Improvement of EPI on the background of taking an enzyme preparation with a minimum lipase activity of 25,000 PhEur units as a part of complex therapy in patients with CP and DM2 is accompanied by pronounced positive dynamics in carbohydrate metabolism and GIH levels. Conclusions. In patients with CP and DM2, the disorders of gastrointestinal hormones have been found, namely, a decrease in gastrin levels and cholecystokinin and an increase in serum somatostatin. The use of a multienzyme drug with a minimum lipase activity of 25,000 PhEur units is an effective means of normalizing clinical and laboratory manifestations of EPI in patients with CP and DM2. The prescription of a multienzyme drug with a minimum lipase activity of 25,000 PhEur units in combination with PPIs in patients with CP and DM2 is a pathogenetically sound method of EPI treatment. It also helps to improve carbohydrate metabolism against the background of normalization of gastrin and somatostatin ratio in these patients.